Cerebral white matter microstructural changes in pure maxillofacial trauma and its associated neuropsychological outcome amongst Malaysian / Sujesh Sreedharan - Sujesh, Sreedharan (2018)
Purpose: The aim of the present study was to establish cerebral white matter (WM) microstructural changes in pure maxillofacial (MF) trauma injuries and the associated neurocognitive deficits in an effort to improve the prognostic values of Diffusion Tensor Imaging (DTI) parameters in mild traumatic brain injury (mTBI) care. Materials and Methods: A prospective review of 21 patients with pure MF was included in the study along with 21 healthy control participants. Magnetic resonance imaging (MRI) and structural DTI were performed on all patients using a 3T MRI (within 24 hours from the time of trauma). The DTI values were registered to the ICBM DTI-81 white matter atlas. Fractional anisotropy (FA), mean diffusivity (MD) and radial diffusivity (RD) values were automatically calculated for 50 white matter tracts. Comprehensive neuropsychological evaluation was done using the Screening – Neuropsychological Assessment Battery (SNAB) within the same admission. After 6 months in average (chronic phase), patients were subjected for a repeat of DTI scan and neuropsychological evaluation. Descriptive statistics were used for the demographic data, and a paired t – test and repeated measure analysis of variance were used to establish the intergroup differences and susceptibility. Results: The included patients were relatively young adults, with a mean age of 29 ± 8.1 years and 13.0 ± 1.2 years of education. Of the 21 patients, 5 (24%) had MF injuries involving the soft tissue, 2 (9%) had MF injury on upper third region, 12 (57%) had injuries at middle third and 2 (10%) were injured on lower third. Of the 21 patients with MF injuries, none had intracranial abnormalities found on the admission CT scan. Executive function and attention were significantly altered across the time points, with patients with MF injury doing poorly at iv baseline with signs of a slowed recovery 6 months later. Wider variety of WM tracts injury responses were noted with radiological evidence of reactive astrogliosis, vasogenic and cytotoxic edema in the acute phase and subsequent demyelination and degeneration of WM tracts over time. The pathogenic processes were strongly correlated with the neuropsychological deficits seen in MF patient group. Conclusion: The unique DTI parameters (both at acute and follow up) enable better prognostication of neuropsychological outcomes in patients with MF injuries. Keywords: maxillofacial injury; diffusion tensor imaging; microstructural changes; traumatic brain injury; neuropsychology